1991
DOI: 10.1007/bf01698376
|View full text |Cite
|
Sign up to set email alerts
|

Serum α2-HS glycoprotein concentration in patients with hematological malignancies

Abstract: We observed significantly reduced serum alpha 2-HS glycoprotein concentrations in patients with acute lymphocytic, acute nonlymphocytic, chronic granulocytic and chronic myelomonocytic leukemias, Hodgkin's and non-Hodgkin's lymphomas, myelofibrosis, and multiple myeloma, but not in patients with chronic lymphocytic leukemia and polycythemia vera, as compared with healthy controls. We followed the serum level of the protein for 18 months. Patients with infectious complications, those receiving cytostatic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…30,31 Furthermore, an increased consumption was also supposed to result in reduced serum AHSG levels in patients with hematological malignancies. 32 In pregnancy, the fetoplacental unit can be another source of the protein. Indeed, AHSG is highly expressed in placental tissues, and a passive transplacental transfer of this substance Decreased serum a 2 -HS glycoprotein level in preeclampsia A Molvarec et al has also been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Furthermore, an increased consumption was also supposed to result in reduced serum AHSG levels in patients with hematological malignancies. 32 In pregnancy, the fetoplacental unit can be another source of the protein. Indeed, AHSG is highly expressed in placental tissues, and a passive transplacental transfer of this substance Decreased serum a 2 -HS glycoprotein level in preeclampsia A Molvarec et al has also been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, circulating AHSG levels decrease in several conditions characterized by tissue damage, infection, inflammation or malignancy. 16,32,[36][37][38] However, other factors may also have contributed to our observation. It has been shown earlier that AHSG enhances the macrophage-mediated phagocytosis of apoptotic cells in vitro by stimulating macropinocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…AHSG is considered as a negative acute phase reactant, the concentration of which decreases during infections, trauma and liver cirrhosis (15)(16)(17). It is tempting to speculate on the biological significance of this protein in clinical settings where its concentration increases, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of human fetuin have been observed in patients with acute lymphocytic leukemia, Hodgkin's and non-Hodgkin's lymphomas, rheumatoid arthritis, acute alcoholic hepatitis, chronic active hepatitis, acute and chronic pancreatitis, inflammatory bowel disease, and trauma (22,43). Under conditions where macrophage-associated fetuin levels are decreased, macrophage deactivation by endogenous counter-regulators may be impaired, leading to uncontrolled overproduction of proinflammatory cytokines.…”
Section: And 115 D-s-s-p-d-s-a-e-d-v-r͞h-k-l͞v-c-p͞q-d͞n͞r 130 )mentioning
confidence: 99%